ANALISIS BIAYA SIKLUS HIDUP JEMBATAN GELAGAR BETON BERTULANG KONVENSIONAL DAN JEMBATAN INTEGRAL PENUH BETON BERTULANG BENTANG 20 METER - , GINA RIZKA AMALIA; , Ir. Heru Budi Utomo, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In conventional reinforced concrete girder bridge there is often an expansion joint and crack between upper-structure and sub-structure. Meanwhile full integral reinforced concrete girder bridge made without any movement between spans or between span and abutments, so there is no expansion joint. With the differences in the structural elements of the bridge, it will affect the needs of bridge maintenance costs during the design life of 50 years. Based on the life cycle cost analysis, the costs that can be determined are maintenance cost, inspection cost, future rehabilitation cost and total life cycle cost over the life plan of the bridge. The method that used in this analysis is future value method of a single payment. In this life cycle cost analysis, the initial cost of a conventional bridge is lower than the initial cost of integral bridges. However, the total life cycle cost of a conventional bridge is much higher than the cost of an integral bridge, which was Rp 30,069,063,000.00 for conventional bridges and Rp 17,946,887,000.00 for integral bridges. Thus, the low initial cost of construction has not determined the total life cycle costs are low.